Կրթական գործընթացի կազմակերպման խոչընդոտները տեխնոլոգիական արդի մարտահրավերների տեսանկյունից - Սյուզաննա Եղիազարյան (ՀՀ ԳԱԱ հրատ.)
Статья рассматривает и детально анализирует проблему препятствий эффективной организации учебного процесса в лице вызовов современных информационных технологий. Suzanna Yeghiazaryan in this article investigates and analysis in detail the hindrances to the effective organization of educational processes in the face of modern information technology challenges.
Keywords: Bibliography; Education; Information resources